Application of Education Management Information System in the Online Learning Process in Madrasah - Danang Dwi Prasetyo; Annisa Himmatul Ilya; Syarif Hidayat; Diningrum Citraningsih (STAI Hubbulwathan Duri, 2023)
Educational institutions will be more advanced and globally competitive with the ability to adapt to the application of management information systems which in the learning process are currently integrating online and offline learning. Therefore, schools must prepare strategies to deal with the negative impacts or problems that may occur from the application of management information systems in online learning. This study aims to analyze the application of management information systems in the online learning process. This type of research is descriptive qualitative research. Data collection techniques use observation, interviews and documentation. This data collection includes interviews, observations, documentation, and questionnaires. Data analysis techniques through data reduction, data presentation, qualitative data analysis, drawing conclusions and data validity. The results of the study explained that the implementation of the management information system using data processing applications, namely EMIS and information technology in supporting the learning process, providing educational services by facilitating learning practices using technological infrastructure, such as learning facilities by combining applications and computers with wifi. The implementation of learning through three stages, namely first, the planning stage by making an effective day analysis and analyzing the learning program by compiling a syllabus, compiling lesson plans, making learning media and preparing other learning tools. Second, the implementation stage, in the implementation stage there are three activities, namely preliminary activities, this activity, and closing activities. Third, evaluation of learning, at this stage assess student learning outcomes in writing, orally, scientific work, tasks and practice. In addition, the teacher makes direct observations to observe the attitudes of students in terms of spirituality, knowledge and skills. This research focuses on online learning where in its management it still takes various efforts to get the right and measurable formula, so that student learning outcomes can be achieved optimally